Some Reflections on the Economic Consequences of the Cancellation of a Contract in French Law - Sage, Yves-Louis; Angelo, Anthony H (Victoria University of Wellington Law Review, 2000)
French law has no general rules on restitution. However, it does have specific restitutionary principles for different areas of law. This article, originally written in French, considers the restitutionary principles that apply in the field of contract.